Glass: Topological Engineering of Glass for Modulating Chemical State of Dopants (Adv. Mater. 47/2014). (December 2014) - Zhou, Shifeng; Guo, Qiangbing; Inoue, Hiroyuki; Ye, Qun; Masuno, Atsunobu; Zheng, Binbin; Yu, Yongze; Qiu, Jianrong
<x xml:space="preserve">Abstract</x> On page 7966, S. F. Zhou and co‐workers report a vital and unprecedented link between the structural constraints of disordered glass and the chemical state of dopants, and propose a milestone approach to modulate the chemical state of the dopants over a wide range of length scales by engineering the topological features of the host glass. Not only does this pioneering approach substantially upgrade the optical performance of a doped material, but it also constitutes a giant step toward the fundamental insight into the origin of the "concentration quenching" phenomenon in luminescent materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>